Dream making in a dream-taking world: 10 surefire strategies to overcome obstacles and live your dreams - "Price, Steve" (Bhopal, 2012)
Dream Making in a Dream Taking World gives you ten proven, time-tested strategies which are used by successful people to achieve their dreams. By using these strategies you can too become a Dream Maker and can make your dreams come true. This book explains how the successful people Dream Makers, get to live their dreams.
Keywords: Personal development